Tradition and gender - Line Førre Grønstad (Nordisk Tidskrift för Socioonomastik)
Until recently, little attention has been given to men’s surname choices in couples. By analysing men’s narratives, this study investigates the motivations and social implications of their choices. Drawing on historical and sociocultural perspectives, it demonstrates how men’s names are privileged in Norwegian culture compared to women’s names despite a high degree of gender equality. Men who break the norms want to make their own decisions. Overall, this research contributes to the broader discourse on gender equality by highlighting the transformative potential of seemingly small acts, such as name choices. It also contributes to socio-onomastics by highlighting surname choice as a meaningful and gendered activity.